Gratitude interventions to improve wellbeing and resilience of graduate nurses transitioning to practice: A scoping review - Pauline Calleja; Pamela Knight-Davidson; Andrew McVicar; Caroline Laker; Stephen Yu; Linda Roszak-Burton (Elsevier, 2024)
Background: New graduate nurses are the nursing cohort at greatest risk for turnover and attrition in every context internationally. This has possibly been heightened during the COVID-19 pandemic. Workplace conditions significantly impact nursing turnover; however, interventions under the positive psychology umbrella may have a mediating impact on the intention to leave. New graduate nurses are generally challenged most in their first three years of clinical practice, and the need for support to transition is widely accepted. Gratitude practice has been reported to improve individual control and resilient response to setbacks and, therefore, is of interest in testing if this intervention can impact turnover intention in the workforce. Objective: To report on a scoping review undertaken to identify whether 'gratitude practice' as an intervention had the potential to improve new graduate nurses' wellbeing and resilience. Methods: Arksey and O'Malley's scoping review approach. Primary research papers of any methodology, published in English between January 2010 and July 2022 were included. Literature was sourced from seven databases, including CINAHL PLUS, ERIC, MEDLINE, Professional Development Collection, APA PsychInfo, APA PsychArticles, and Psychological and Behavioural Sciences Collection. Results: We identified 130 records, of which we selected 35 for inclusion. A large range of interventions were identified; most had some form of writing, journaling, or diarising. The next most common intervention was teaching gratitude strategies via workshops, and many interventions had some form of list or activity trigger for participants to complete. Five studies had complex combined interventions, while the rest were simple, easily reproducible interventions. Interventions were delivered both face-to-face or asynchronously, with some being online only and others sent out as a 'kit' for participants to work through. Conclusion: Our review of existing literature shows a significant gap in research on gratitude practice and its impact on nursing populations. To ensure robust future studies, we suggest defining concepts clearly and selecting outcome measures and tools that are not closely related. Intervention design may not be as important as the choice of measures and tools to measure outcomes.